2007
DOI: 10.2139/ssrn.963965
|View full text |Cite
|
Sign up to set email alerts
|

Are Voters Sensitive to Terrorism? Direct Evidence from the Israeli Electorate

Abstract: This product is part of the RAND Labor and Population working paper series. RAND working papers are intended to share researchers' latest findings and to solicit informal peer review. They have been approved for circulation by RAND Labor and Population but have not been formally edited or peer reviewed. Unless otherwise indicated, working papers can be quoted and cited without permission of the author, provided the source is clearly referred to as a working paper. RAND's publications do not necessarily reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
137
6
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(155 citation statements)
references
References 37 publications
10
137
6
2
Order By: Relevance
“…Berrebi and Klor found that terrorism caused an increase in the relative support for political parties from the right end of the political spectrum, which place more weight on terrorism-deterrence policies. In addition, their conclusions supported the idea that terrorism polarises the electorate (Berrebi 2008). For example, their study showed that terrorism causes an increase in support for the right bloc in all localities with right-leaning preferences and a decrease in support for the right bloc in all localities with left-leaning preferences.…”
Section: Terrorism and Political Preferencessupporting
confidence: 52%
“…Berrebi and Klor found that terrorism caused an increase in the relative support for political parties from the right end of the political spectrum, which place more weight on terrorism-deterrence policies. In addition, their conclusions supported the idea that terrorism polarises the electorate (Berrebi 2008). For example, their study showed that terrorism causes an increase in support for the right bloc in all localities with right-leaning preferences and a decrease in support for the right bloc in all localities with left-leaning preferences.…”
Section: Terrorism and Political Preferencessupporting
confidence: 52%
“…In the incidence regressions we find that it is the second lag on days with successful suicide 13 Some recent studies provide empirical support to the notion that violence radicalizes the victimized population: Berrebi and Klor (2007) document that Israeli voters are more likely to vote for right-wing parties in response to Palestinian terrorist attacks; find that violence against Palestinians leads to a decrease in support for the moderate Fatah faction. 14 In these robustness tests we experiment with a number of different transformations of the dependent variable "total Palestinian fatalities."…”
mentioning
confidence: 60%
“…Such negative effects may feed through to a reduction of overall economic growth (Crain and Crain 2006;Gaibulloev and Sandler 2008). It may also produce political costs, e.g., by affecting government stability (Gassebner, Jong-A-Pin and Mierau 2008) or voter behavior (Berrebi and Klor 2008). regularly use terror as a means to meet other objectives. The main hypothesis is that terror is more easily generated in those parts of the world where poor socio-economic conditions and institutions prevail.…”
Section: Introductionmentioning
confidence: 99%